Causes and Consequences of Organizational Cynicism (Case Study: Employees of Parsian Electronic Commerce Company) - Mehdi Haghighi Kafash; Nader Mazloumi; Farzaneh Mirzamohammadi (مطالعات مدیریت بهبود و تحول, 2011)
Should the human resource managers be concerned about cynicism and should they attempt to respond to it or not, depends mostly on whether cynicism has any negative effects on employees or their organizations. Many researchers have found that there is a relation between organizational cynicism and many variables such as job satisfaction, organizational commitment, organizational alienation, and organizational citizenship behavior. As many studies have shown, Cynicism has been associated with negative consequences respectingthe employees. Employees that are cynical about their organization, experience a variety of negative emotions, including distress, disgust and even shame when they think of their organizations. Thesenegative emotions result in emotional fatigue and depression. In this study it is attempted to investigate the causes and consequences of organizational cynicism in the Parsian Electronic Commerce Company. For the testing of research hypotheses, structural equation model (SEM) was used. The test results indicated that psychologicalcontract violation, organizational justice, and perceived organizationalsupport, affect the employee’s organizational cynicism; also thatorganizational cynicism has an effect on employee’s organizationalcommitment, organizational citizenship behavior, and theircounterproductive work behavior.